Molecular cloning and functional characterization of NtWRKY41a in the biosynthesis of phenylpropanoids in Nicotiana tabacum - Wang, Zhong (Plant science : an international journal of experimental plant biology, 2022)
Copyright © 2021 Elsevier B.V. All rights reserved.